2002
DOI: 10.1046/j.1460-9568.2002.01995.x
|View full text |Cite
|
Sign up to set email alerts
|

Cell‐specific expression of the glutamine transporter SN1 suggests differences in dependence on the glutamine cycle

Abstract: Glutamine is involved in a variety of metabolic processes, including recycling of the neurotransmitters glutamate and gamma-aminobutyric acid (GABA). The system N transporter SN1 mediates efflux as well as influx of glutamine in glial cells [Chaudhry et al. (1999), Cell, 99, 769-780]. We here report qualitative and quantitative data on SN1 protein expression in rat. The total tissue concentrations of SN1 in brain and in kidney are half and one-quarter, respectively, of that in liver, but the average concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
131
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 130 publications
(149 citation statements)
references
References 85 publications
(121 reference statements)
17
131
1
Order By: Relevance
“…SNAT3 is highly expressed in brain astrocytes, and is believed to play a role in the glutamate-glutamine cycle involved in neurotransmission [5,15,22]. The lethargy and an altered, uncoordinated gait observed in mutant mice suggested impaired neurotransmission after Snat3 deletion in brain.…”
Section: The Glutamate-glutamine Cycle Is Defective In the Brain Of Smentioning
confidence: 99%
See 1 more Smart Citation
“…SNAT3 is highly expressed in brain astrocytes, and is believed to play a role in the glutamate-glutamine cycle involved in neurotransmission [5,15,22]. The lethargy and an altered, uncoordinated gait observed in mutant mice suggested impaired neurotransmission after Snat3 deletion in brain.…”
Section: The Glutamate-glutamine Cycle Is Defective In the Brain Of Smentioning
confidence: 99%
“…have been hypothesized to be responsible for the efflux of glutamine from astrocytes which is a crucial step in the recycling of glutamate and GABA neurotransmitters between astrocytes and neurons [5,22]. In the liver, SNAT3 is likely to be a candidate for both periportal uptake and perivenous efflux of glutamine, which is essential for the detoxification of ammonia delivered via the portal blood and excreted as urea [6,21].…”
Section: Introductionmentioning
confidence: 99%
“…The molecular bases of Gln passage across the astrocytic membrane and neuronal plasma membranes have been investigated extensively over the last few years [12,20,44]. Gln efflux from astrocytes appears to be mediated by sodium-coupled neutral amino acid transporter 3 (SNAT3, SN1), a system N amino acid transporter that is localized to perisynaptic astrocytes and specifically accepts only glutamine, histidine and asparagine [13,19,21]. Gln uptake into neurons is mediated by sodium-dependent transporters of the system A family, two of which, SNAT1 (GlnT, SAT1, ATA1, SA2) and SNAT2 (SAT2, ATA2), are thought to be capable of affecting Glu and/or GABA recycling, and, thereby, synaptic function.…”
Section: Introductionmentioning
confidence: 99%
“…SN1 was the first isoform characterized and it has been described as the primary transporter responsible for the release of glutamine from astrocytes. It preferentially transports glutamine, promoting its efflux under physiological concentrations of this amino acid (~400 μM) (Boulland et al, 2002;Chaudhry et al, 1999). One important property of this amino acid transporter is its capacity of flux reversal, which is dependent on pH and also on the extracellular Na + concentration, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of this transporter in relation to the glutamate/GABA-glutamine cycle is highlighted by the observation that exogenous glutamate mediates a decrease in the Km for SN1 in astrocyte cultures (Bröer et al, 2004). Similarly, the SN2 isoform is also functionally related to glutamine efflux from astrocytes, although it also releases glycine serving as a co-transmitter at NMDA receptors Hamdani et al, 2012).With respect to the CNS localization of these transporters, SN1 has been shown to be confined to astroglial processes ensheathing glutamatergic and GABAergic synapses in different brain structures (Boulland et al, 2002;Chaudhry et al, 1999), while SN2 has also been found in astrocytes predominantly close to glutamatergic synapses .…”
Section: Introductionmentioning
confidence: 99%